Lancaster skies - Burn, Callum; Burn, Andrew; Parsons, Sam; Mundell, Jeffrey; Dobson, David; Collie, Henry; Gale, Joanne; Shout! Factory (Firm); Kaleidoscope Entertainment (Firm : Great Britain); Tin Hat Productions (Los Angeles, CA Shout Factory, 2020)
Douglas Miller, a broken, solitary Spitfire ace who survived the Battle of Brditain, transfers to Bomber Command, determined to take the war to the skies over Nazi Germany. Miller must take the place of a Lancaster bomber crew's cherished and respected skipper, who was killed in action. Though the crew is against him, he will try to gain their trust and overcome the darkness in his past to become the leader they so desperately need in the pivotal aerial battles that await them over Berlin.
Originally released as a motion picture in 2019.
Widescreen (2.39:1)
Original score by James Griffiths ; director of photography, Sam Parsons.
Jeffrey Mundell, David Dobson, Henry Collie, Joanne Gale.
Not rated.
DVD; widescreen; region 1, NTSC; Dolby Digital 5.1 & stereo.
Keywords: Great Britain. -- Royal Air Force. -- Bomber Command -- Drama; 1939-1945; Lancaster (Bomber) -- Drama; World War, 1939-1945 -- Aerial operations, British -- Drama; Military operations, Aerial -- British; Video recordings for the hearing impaired; War films; Historical films; Drama; Feature films; Fiction films